The Effect of Organizational Culture on Student Social Character at Al Ghifari Integrated Junior High School, Sukabumi Regency - Najrul Jimatul Rizki; Kun Nurachadijat (P3M IAI Nusantara Batang Hari, 2023)
This study aims to analyze the influence of organizational culture on students' social character. Cultural organizations can play an important role in shaping the social character of individuals, including students in educational settings. Strong social character in students not only influences their interpersonal relationships, but also forms a solid foundation for their future lives. This study uses a qualitative approach in collecting data. Meanwhile, qualitative data were obtained through in-depth interviews with students, teachers, and school administration staff who were selected purposively. The results of the study show that positive and inclusive cultural organizations have a significant influence on students' social character. Schools that encourage cooperation, mutual respect, and caring among students tend to produce students who are more empathetic, outgoing, and responsible. In addition, the role of teachers and school administrative staff has also proven to be very important in shaping the social character of students. Teachers who are good role models, provide positive guidance, and create safe and inclusive environments can have a positive impact on the social character of students. Likewise, school administration staff who build a positive and supportive school climate make a significant contribution to the development of students' social character. Based on these findings, the recommendation to increase the influence of organizational culture on students' social character is to encourage schools to adopt and strengthen an organizational culture that is inclusive, mutually protective, and oriented to social interests.